2007
DOI: 10.1007/s00464-007-9293-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of autologous platelet–leukocyte gels to enhance the healing process in surgery, a review

Abstract: Background: The therapeutic use of autologously prepared, platelet-leukocyte-enriched gel (PLG) is a relatively new technology for the stimulation and acceleration of soft tissue and bone healing. The effectiveness of this procedure lies in the delivery of a wide range of platelet growth factors mimicking the physiologic wound healing and reparative tissue processes. Despite an increase in PLG applications, the structures and kinetics of this autogenously derived biologic material have not been observed. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 55 publications
1
64
2
Order By: Relevance
“…These findings in consistence with literature that PRP increases growth factors and through this mechanism speeds up wound healing 27,28 . In many studies that have been carried out, concentrated growth factors have been found to speed up wound healing at a rate of 30-40% 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings in consistence with literature that PRP increases growth factors and through this mechanism speeds up wound healing 27,28 . In many studies that have been carried out, concentrated growth factors have been found to speed up wound healing at a rate of 30-40% 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it possesses antimicrobial properties that may contribute to the prevention of infections [2].…”
Section: Discussionmentioning
confidence: 99%
“…This may be a promising technique that could support and promote bone growth and accelerate fracture healing, particularly in patients who are at risk of the development of non-unions [1]. PRP is promoted as an ideal autologous prepared biological blood derived product, which can be exogenously applied to a diversity of tissues where it releases high concentrations of platelet growth factors that enhance bone healing [2].…”
Section: Introductionmentioning
confidence: 99%
“…In this environment, the biologically active proteins might bind to specific platelet growth factor receptors present in surgical tissues. Released growth factors interact and bind with the platelet tyrosine kinase receptor (TKR), which is present in the cell membranes of tissue cells (ligand-receptor interaction) (21). Therefore, the actual binding site is on the outer surface of the cell membrane, and thus not directly on the cell nucleus.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%